Bidder selection by type of reverse auction colombian government contracting (2015)
The recruitment history of Colombia and especially the abbreviated mode type selection via Reverse Auction with their advantages and disadvantages based on Decree 734 of 2012 (Group, 2012, pp.15-19), Act 1510 of 2013 (Group, 2013, pp.20-23) and decree 1082 of 2015 (planning, 2015, pp.20-26), fundamental concepts that allow on the procedures for contracting with state agencies to purchase goods and services features technical uniform and common use.